Assessing Foreign Aid's Long-Run Contribution to Growth and Development. (May 2015) - Arndt, Channing; Jones, Sam; Tarp, Finn
Summary: This paper confirms recent evidence of a positive impact of aid on growth and widens the scope of evaluation to a range of outcomes including proximate sources of growth (e.g., physical and human capital), indicators of social welfare (e.g., poverty and infant mortality), and measures of economic transformation (e.g., share of agriculture and industry in value added). Focusing on long-run cumulative effects of aid in developing countries, and taking due account of potential endogeneity, a coherent and favorable pattern of results emerges. Aid has over the past 40 years stimulated growth, promoted structural change, improved social indicators, and reduced poverty.